Decision Support System for New Employees Candidat Selection PT. Dawam Prima Perkasa Using Aras Method Web Based - Saifur Rohman Cholil; Enggar Satrio Prisiswo (School of Industrial and System Engineering, Telkom University, 2020)
Employees are one of the supporting factors for a company, because by having qualified employees,according to the qualifications and criteria needed by the company, then the company can develop and moveforward in the future. No exception, PT. Dawam Prima Perkasa who is in need of new employees who aresuitable to work in the company. However, PT. Dawam Prima Perkasa is faced with a problem where thelarge number of prospective employees who take the selection test will cause the number of incoming filesto be adjusted to the criteria owned by the company and require a lot of time, making it prone to file errors.To minimize the occurrence of errors and the length of time used, a Decision Support System was created todetermine the best prospective employees who will work in the company. The Decision Support SystemMethod used is the Additive Ratio Assessment (ARAS). This research has gone through the process ofvalidating the Spearman rank correlation and the value is 0.950. Based on these results, the ARAS methodcan be used in selecting prospective new employees at PT. Dawam prima Perkasa.